2017
DOI: 10.1101/213868
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An eutherian intronic sequence gave rise to a major satellite DNA in Platyrrhini

Abstract: Satellite DNAs (satDNAs) are major components of eukaryote genomes. However, because of their quick divergence, the evolutionary origin of a given satDNA family can rarely be determined. Herein we took advantage of available primate sequenced genomes to determine the origin of the CapA satDNA (~1,500 bp long monomers), first described in Sapajus apella. We show that CapA is an abundant satDNA in Platyrrhini, whereas in the genomes of most eutherian mammals, including humans, this sequence is present only as a … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
(16 reference statements)
0
1
0
Order By: Relevance
“…A parallel line of research has focused on elucidating satDNA evolution using molecular and cytogenetic methods. These studies confirmed that satellite repeats can be generated by tandem amplification of various genomic sequences, for example, parts of dispersed repeats within potato centromeres (Gong et al , ) or a single‐copy intronic sequence in primates (Valeri et al , ). An additional putative mechanism of satellite repeat origin was revealed in DNA replication studies, which showed that repair of static replication forks leads to the generation of tandem repeat arrays (Kuzminov, ).…”
Section: Introductionmentioning
confidence: 57%
“…A parallel line of research has focused on elucidating satDNA evolution using molecular and cytogenetic methods. These studies confirmed that satellite repeats can be generated by tandem amplification of various genomic sequences, for example, parts of dispersed repeats within potato centromeres (Gong et al , ) or a single‐copy intronic sequence in primates (Valeri et al , ). An additional putative mechanism of satellite repeat origin was revealed in DNA replication studies, which showed that repair of static replication forks leads to the generation of tandem repeat arrays (Kuzminov, ).…”
Section: Introductionmentioning
confidence: 57%